Subsessila turbinata gen. et. sp. nov. (Beltraniaceae), a Beltrania-like fungus from Thailand - Chuan Gen Lin (2018)
© 2017, German Mycological Society and Springer-Verlag Berlin Heidelberg. A new monotypic Beltrania-like genus, Subsessila, with its type species S. turbinata, is described, illustrated and compared with similar genera. The new genus is introduced in the family Beltraniaceae based on phylogenetic analysis and morphological characters. Subsessila can be easily distinguished from other Beltrania-like genera by dark setae arising from radially lobed basal cells, mostly lacking macronematous conidiophores. Conidiogenous cells are ampulliform or doliiform and produce turbinate to clavate conidia with rostrate proximal end and rounded distal end. Evidence for establishment of the new genus is provided based on morphological comparison and DNA sequence data analyses.